In vitro Assessment of Period of Oviposition and Hatching in Hyalomma anatolicum anatolicum - Akil, Mohd; Bagherwal, RK; Jayraw, AK; Rajput, N; Singh, R (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Hyalomma anatolicum anatolocum is one of the most important tick species in India (Geeverghese and Dhanda,  1987), which assumed noticeable importance because of its  role as the major vector of the hemoprotozoan parasites.  Besides, the role of Hyalomma species in transmitting the  Crimean-Congo hemorrhagic fever (CCHF) virus in humans  has been established in different countries (Karti et al., 2004).  Ticks produce severe economic losses through blood-sucking  and acting as vectors of pathogens and toxins. In India alone,  the cost of tick and tick-borne diseases (TTBDs) in animals has  been estimated to the tune of approx. Two thousand crores  (Ghosh et al., 2007). Scanty literature is available pertaining to  the life cycle of H. a. anatolicum in general and from Madhya  Pradesh in particular. Therefore, the present study was  designed to record the period of oviposition and hatching  of eggs in H. a. anatolicum.
Keywords: Hatching period; Hyalomma anatolicum anatolicum; Period of oviposition